Esterase profile in a pyrethroid-resistant Brazilian strain of the cattle tick Boophilus microplus (Acari, Ixodidae) - Baffi, Milla Alves [UNESP]; Pereira, Cícero Donizete; Souza, Guilherme Rocha Lino de; Bonetti, Ana Maria; Ceron, Carlos Roberto [UNESP]; Gourlart, Luiz Ricardo (Sociedade Brasileira de Genética, 2005)
The cattle tick Boophilus microplus causes great damage in livestock and is considered one of the most important tropical ectoparasites. The traditional method of control is based on the intensive use of pesticides, however the indiscriminate use of these compounds over the years has led to the selection of resistant ticks. Hydrolases, particularly esterases (EST), have been reported to be associated with acaricide resistance in B. microplus. We compared the esterase profile of susceptible and cypermethrin-resistant strains of adult B. microplus and a pyrethroid susceptible reference strain (the Mozzo strain) using polyacrylamide gel electrophoresis and specific staining. The electrophoretic profiles of protein extracts revealed the presence of four regions with esterase activity in the cypermethrin-resistant strain and three of these regions in the susceptible strains. The bands were numbered EST-1 to EST-4 in sequence (starting from the anode) according to their decrease in negative charge. The EST-1A and EST-1B enzymes were detected only in the resistant strain. The inhibition studies with eserine sulfate, copper sulfate, p- p-chloromercuribenzoate (pCMB), malathion and phenylmethylsulfonyl fluoride (PMSF) indicated that the EST-1A and EST-1B enzymes belong to the acetylcholinesterase class and are probably associated with resistance to acaricides in this Brazilian resistant strain of B. microplus.
Keywords: Boophilus microplus; Pesticide; Resistance; Esterase